Velocity weapon - O'Keefe, Megan E., 1985- (O'Keefe, Megan E., 1985- Protectorate, 2019)
The last thing Sanda remembers is her gunship breaking up around her as HER evac pod expanded, sealing her away for salvage-medics to pick up. She wakes up 230 years later on an empty enemy smartship, The Light of Berossus-- or Bero, as he prefers to be called. The war is lost. The star system is dead. But in the vastness of space, anything is possible.... -- adapted from back cover